Jurisdictional Consequences of Government Administration Law on the Implementation of Duties and Authorities of the Financial Audit Agency - Nizam Burhanuddin; Dwi Putri Cahyawati (Warmadewa Press, 2022)
In the perspective of administrative law, the existence of a state agency BPK is a manifestation of the existence of another form of power from state power, namely the power of supervision of state finances or power of inspection. In carrying out its duties and authorities to examine the management and responsibilities of state finances, BPK is often faced with problems that are closely related to the dynamics of law and legislation. Authority disputes, overlapping regulations, to technical matters related to inspection procedures are examples of some of these problems. Problems that have been and will continue to exist along with development developments that demand the birth of new legal dynamics that are increasingly complex. To the development of administrative law. Law Number 30 of 2014 concerning Government Administration which applies to all government functions contained in Ministries and Institutions has juridical consequences from this to the implementation of government administration contained in BPK, thus regarding the delegation of authority from BPK to BPK Implementers must be clearly regulated in BPK's legal products.